Relationship between achievement in selected high school subjects and performance in the NCEE and the UP College Admission Test - Mocorro, Zenaida Gonzalez 1946- (1977)
This study was designed to determine the relationship between achievement in selected high school subjects and performance in the National College Admission Test and the University of the Philippines College Admission Test. Achievement in high school was represented by the average of final grades from first to fourth year, for each of Mathematics, Science and English. The results of the study showed that there existed very high relationship between achievement in high school and performance in the NCEE and UPCAT. From the results, it appeared that achievement in Mathematics and English is indicative of performance in the NCEE and UPCAT. In science, however, teacher evaluation of many students did not correspond to students' performance in the two tests.